Desmoplastic Small Round Cell Tumor: Pathology, Genetics, and Potential Therapeutic Strategies. (December 2016) - Thway, Khin; Noujaim, Jonathan; Zaidi, Shane; Miah, Aisha B.; Benson, Charlotte; Messiou, Christina; Jones, Robin L.; Fisher, Cyril
Desmoplastic small round cell tumor (DSRCT) is an aggressive small round cell neoplasm which predominantly occurs intra-abdominally in adolescents and young adults with a male predominance, and which is characterized by a recurrent t(11;22)(p13;q12) translocation leading to formation of the EWSR1-WT1 fusion gene, which generates a chimeric protein with transcriptional regulatory activity. Histologically, DSRCT has a characteristic morphology, of islands of monotonous small cells within prominent sparsely cellular fibroblastic stroma, and immunohistochemically it shows polyphenotypic multidirectional differentiation, with expression of epithelial, muscle, and neural markers. However, DSRCT can arise more rarely in other sites and exhibit a spectrum of both histologic features and immunoprofile, which may confuse diagnosis with other small round cell neoplasms. Correct diagnosis is important to ensure correct treatment and prognostication; DSRCT are almost universally fatal neoplasms with patients usually succumbing to disease within the first 2 years of diagnosis. While combination treatment strategies can confer a survival benefit, the overall prognosis remains poor. Further insight into the tumorigenic molecular changes generated by the fusion oncogene may lead to the generation of specific targeted therapies. We review DSRCT, discussing morphology and immunohistochemistry, molecular genetic findings, potential targeted treatments, and the differential diagnosis.